The importance of vocational guidance for adolescents in choosing a profession - Beisenbayeva Zh. А.; Sangilbayev, O. S.; Mustafa, T. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
The article deals with the most important features of professional orientation of adolescents in peda- gogical and psychological terms. Today, the problem of adaptation and proper orientation of adolescents to the choice of a profes- sion through self-knowledge arises. An educator-psychologist plays an important role in revealing all the abilities and capabilities of a person, teaching them a healthy lifestyle, and creating a culture of com- munication, they must provide the necessary assistance to adolescents in a conscious choice of a future profession, taking into account the peculiarities of their psychological development. Vocational guidance is an activity aimed at preparing adolescents for the choice of profession, tak- ing into account their individual inclinations, interests, professional hobbies and society’s requests for personnel of various levels and qualifications. The essence of professional orientation as a social problem is the professional desire of adolescents to overcome contradictions, the demand of society in personnel. In solving this contradiction, a key role is played by the actions and activities of the teaching staff, teachers, psychologists responsible for labor and vocational training of students. On its basis, the level of theoretical development, the principles of professional orientation and methodological problems are formed. Thus, adolescents should be open in choosing a profession, more consciously understand what is necessary in their future life, use all the opportunities for a conscious and correct choice of a future profession. Key words: teenager, professional orientation, psychophysiological questionnaires, motivation, training, cognitive principle, education, activity.